REFLEKSI RASA SIMPATI DALAM NOVEL NARASI 2021 KARYA TENDERLOVA - Gani, Abdul; Maulinda, Aisyah Nurul; Fasah, Lukmanul Hakim; Mas’odi, Mas’odi; Nisa’, Tarisatun (Jurnal Membaca Bahasa dan Sastra Indonesia, 2025)
This research aims to identify a reflection of sympathy contained in the object, namely the novel Narasi 2021, using qualitative descriptive methods and a structuralism approach. The source of this research is a fiction book, namely an inspirational novel by Tenderlova which is a bilogy of her first novel, namely "Literature Writing". The author will review the form of reflection of sympathy contained in the novel Narasi 2021 by Tenderlova. This research will then explain the form of reflection of sympathy contained in the novel in the form of 1). Dialogue 2). Attitude or behavior.